Cryptographic security analysis of the shift password method using the google colab application - Rokhim Utomo; Mokhammad Syafaat; Kasiyanto Kasiyanto; Dekki Widiatmoko; Rafi Maulana (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2025)
The study of information security methods to prevent unauthorized parties from reading it is known as cryptography. The Caesar Cipher method is a low-tech yet well-established cryptography technique. One of the earliest and most basic cryptographic methods is the Caesar Cipher, which substitutes a different letter with a specific alphabetic difference for each letter in the text. The Caesar Cipher is simple to comprehend and use, but it has a lot of flaws that leave it open to frequency analysis and brute force attacks. The purpose of this study is to use the Google Colab tool to examine the cryptographic security of the Caesar Cipher technique. In this study, Google Colab—a platform that offers a robust and user-friendly Python programming environment—was utilized to construct and evaluate the Caesar Cipher algorithm. This study design combines an experimental strategy with a descriptive method. The Caesar Cipher technique is put into practice, encryption and decryption simulations are run, and character frequency analysis and brute force assaults are used to analyze security flaws. The study's findings demonstrate that the character distribution pattern is preserved when character frequencies in the original and encrypted text are seen, making it simple for attackers to use frequency analysis to crack the password. This suggests that, in the context of high information security, the Caesar Cipher should not be used. Shift passwords are therefore inappropriate for use in contemporary security applications due to their serious flaws